Edukasi Penggunaan Jaringan Wifi yang Aman dan Efisien di Rumah : Studi Kasus Sosialisasi pada Remaja Desa Darmakradenan, Karangpucung - Juwita Septiani; Vevinciya Dila Dita; Alfi Nazilatun Muntafi’ah; Stella Putriseptiyani Septeragil (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The use of WiFi networks at home has become an essential need in the digital era, but many people still do not understand how to use it optimally and safely. This socialization activity aims to improve digital literacy, especially in managing household WiFi networks, for teenagers who are members of youth organizations in Darmakradenan Village, Karangpucung. The methods   used include presentations, interactive discussions, and distribution of educational modules. The results of the activity showed an increase in participants' understanding of basic network security steps, signal management, and awareness of their role as information technology agents. This activity is expected to contribute to creating a safer and more productive digital ecosystem at the community level.